T Cell Specific BOB.1/OBF.1 Expression Promotes Germinal Center Response and T Helper Cell Differentiation - Betzler, Annika C.; Ezić, Jasmin; Abou Kors, Tsima; Hoffmann, Thomas K.; Wirth, Thomas; Brunner, Cornelia (Frontiers in Immunology, 2022)
The transcriptional co-activator BOB.1/OBF.1 is expressed in both B and T cells. The main characteristic of conventional BOB.1/OBF.1 deficient mice is the complete absence of germinal centers (GCs). This defect was mainly attributed to the defective B cell compartment. However, it is unknown whether and how BOB.1/OBF.1 expression in T cells contributes to the GC reaction. To finally clarify this question, we studied the in vivo function of BOB.1/OBF.1 in CD4+ T and follicular T helper (TFH) cell subpopulations by conditional mutagenesis, in the presence of immunocompetent B lymphocytes. BOB.1/OBF.1 deletion in CD4+ T as well as TFH cells resulted in impaired GC formation demonstrating that the impaired GC reaction described for conventional BOB.1/OBF.1-deficient mice cannot exclusively be traced back to the B cell compartment. Furthermore, we show a requirement of BOB.1/OBF.1 for T helper (TH) cell subsets, particularly for TFH cell differentiation.